Acting on Hormone Receptors with Minimal Side Effect on Cell Proliferation: A Timely Challenge Illustrated with GLP-1R and GPER - Gigoux, Véronique; Fourmy, Daniel (Frontiers in Endocrinology, 2013)
G protein coupled receptors (GPCRs) constitute a large family of receptors that sense molecules outside the cell and activate inside signal transduction pathways and cellular responses. GPCR are involved in a wide variety of physiological processes, including in the neuroendocrine system. GPCR are also involved in many diseases and are the target of 30% of marketed medicinal drugs. Whereas the majority of the GPCR-targeting drugs have proved their therapeutic benefit, some of them were associated with undesired effects. We develop two examples of used drugs whose therapeutic benefits are tarnished by carcinogenesis risks. The chronic administration of glucagon-like peptide-1 (GLP-1) analogs widely used to treat type-2 diabetes was associated with an increased risk of pancreatic or thyroid cancers. The long term treatment with the estrogen antagonist tamoxifen, developed to target breast cancer overexpressing estrogen receptors ER, presents agonist activity on the G protein-coupled estrogen receptor GPER which is associated with an increased incidence of endometrial cancer and breast cancer resistance to hormonotherapy. We point out and discuss the need of pharmacological studies to understand and overcome the undesired effects associated with the chronic administration of GPCR ligands. In fact, biological effects triggered by GPCR often result from the activation of multiple intracellular signaling pathways. Deciphering which signaling networks are engaged following GPCR activation appears to be primordial to unveil their contribution in the physiological and physiopathological processes. The development of biased agonists to elucidate the role of the different signaling mechanisms mediated by GPCR activation will allow the generation of new therapeutic agents with improved efficacy and reduced side effects. In this regard, the identification of GLP-1R biased ligands promoting insulin secretion without inducing protumoral effects would offer therapeutic benefit.